First identification and genotyping of Enterocytozoon bieneusi in humans in Myanmar - Shen, Yujuan (BMC Microbiol, 2020)
BACKGROUND: Intestinal pathogen infections are widespread among impoverished populations. Enterocytozoon bieneusi is the most common pathogen of intestinal microsporidian species in humans worldwide. However, no epidemiological information is available on E. bieneusi infection in humans in Myanmar. The present study comprised the first identification and genotyping of E. bieneusi in humans conducted in Myanmar. RESULTS: A total of 172 fecal specimens were collected from the Wa people (one each) in four villages of Pangsang Township of the Matman District of Shan State, Myanmar, and each participant completed a questionnaire. E. bieneusi was identified and genotyped using polymerase chain reaction (PCR) and sequence analysis of the internal transcribed spacer (ITS) region of the ribosomal RNA (rRNA) gene. The average prevalence of E. bieneusi was 8.72% (15/172), ranging from 3.85 to 13.89% by village. E. bieneusi infection was not related to any of the risk factors studied. Six genotypes were identified, comprising two known genotypes Peru6 (n = 10) and D (n = 1) and four novel genotypes (MMR23, MMR25, MMR86, and MMR87) (one each), and two people infected with genotype Peru6 were from the same family. A phylogenetic analysis based on a neighbor-joining tree of the ITS sequences of E. bieneusi indicated that all the six genotypes were clustered into group 1. CONCLUSIONS: This is the first identification and genotyping of E. bieneusi in humans in Myanmar. The observations that the two people infected with genotype Peru6 were from the same family, and that all six genotypes obtained in the present study fell into zoonotic group 1, showed the potential for anthropogenic and zoonotic transmissions. The present data argue for the importance of epidemiological control and prevention from medical sectors.